2004
DOI: 10.1136/gut.2003.036418
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and subclinical intestinal inflammation assessed by the mucosal patch technique: studies of mucosal neutrophil and eosinophil activation in inflammatory bowel diseases and irritable bowel syndrome

Abstract: Background and aims: There is a clear need for a rapid, simple, safe, and sensitive method of determining the type and intensity of inflammation in the gut mucosa in clinical practice. In this study, we have evaluated the potential of a new method, the mucosal patch technique, in patients with and without apparent gut inflammation, as assessed by conventional diagnostic procedures. Subjects and methods: The technique tested is based on the idea that inflammatory mediators released from the rectal mucosa can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 35 publications
6
53
2
2
Order By: Relevance
“…Post-infectious low-grade mucosal inflammation is thought to be one of several possible causes of IBS in a specific subset of patients (4)(5)(6)(7). IBS has a heterogeneous clinical presentation that includes abnormal bowel movements and abdominal pain, which are also symptoms of inflammatory bowel disease (IBD) (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Post-infectious low-grade mucosal inflammation is thought to be one of several possible causes of IBS in a specific subset of patients (4)(5)(6)(7). IBS has a heterogeneous clinical presentation that includes abnormal bowel movements and abdominal pain, which are also symptoms of inflammatory bowel disease (IBD) (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an increased number of degranulated eosinophils in the upper and lower LP may be a previously unrecognized feature of IBD. Previous studies indicate that eosinophil granule proteins (eg, eosinophil cationic protein, major basic protein) released by activated eosinophils contribute to tissue damage and inflammation during GI disorders and may be indicative of active ongoing disease 3, 10, 30, 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies have demonstrated that normal values of IgE antibodies against food antigens in skin or serum do not exclude an intestinal food allergy [25, 26]. In the present study, we aimed to further investigate the role of inflammation markers in a single provocation model.…”
Section: Discussionmentioning
confidence: 99%